The enhancement of kaempferol by yeast elicitor in calluscultures of Oxystelma Esculentum (L.F). - DEVI MALIGA .K,; YOGANANTH .N, (International Journal of Pharma and Bio Sciences, 2018)
The present investigation is the comparative analysis of kaempferol from the field grown plant parts and in vitro callus through which the enhancement of kaempferol by the influence of yeast elicitor were determined. The stem explants showed highest percentage of callus induction (74.34 + 0.67) and stem explants showed the highest callus growth in terms of fresh weight (3.90 + 0.05 g) and dry weight (0.41 + 0.01g). The maximum content of kaempferol in three type of samples was observed in this order; yeast elicitor treated samples>in vitro raised callus samples> field grown samples. The highest amount of kaempferol was found in 2 ml yeast elicitor treated with stem callus sample (0.958 mg/g. dry weight). Hence, from the current investigations, it was proved that the highest amount of kaempferol was observed in elicitor treated in vitro callus is provides resource for valuable drugs preparation against various diseases.